Effect of transplanting time on growth and marketable curd yield of different cultivars of cauliflower (Brassica oleracea var botrytis subvar cauliflora) under dry temperate high hill conditions - SHARMA, AKHILESH; PATHANIA, N K; SHARMA, SUSHEEL; PATHAK, SANJEEV (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted at experimental farm of Highland Agricultural Research and Extension Centre of Chaudhary Sarwan Kumar Himachal Pradesh Krishi Vishvavidyalaya , Kukumseri (Lahaul and Spiti) during summers of 2001 and 2002 to find out the optimum time oftransplanting for cauliflower (Brassica oleracea L. var botlytis L. subvar cauliflora DC.) cultivars. The experiment consisted of treatment combinations of3 planting dates (18 May, 2 June and 17 June) and 3 cultivars ('Pusa SnowballK 1', 'Palam Uphar' and 'Pusa Himjyoti'). Transplanting of cauliflower cultivars on 2 June gave tpe maxinlum plant survival. The marketable curd yield (20.9 tonneslha) was highest on 2 June transplanting along with maximum net returns (Rs 0.211 million/ha). The variety 'Pusa Snowball K I' (20.7 tonnes/ha) significantly outyielded the 'Palam Uphar' (17.8 tonneslha) and 'Pusa Himjyoti' (16.6 tonnes/ha) along with its better performance for curd and plant attributes. The interaction effects indicated that transplanting of 'Pusa Snowball K l' on 2 June gave the maximum marketable curd yield (24.7 tonnes/ha) combined with better performance for average curd weight, gross and net curd weight, curd diameter and curd size index. The maximum net returns (Rs 0.257 millionlha) and B: C ratio (6.4: 1) were also obtained from the same combination.